Hydration catalyst, preparation method and application thereof, and epoxy compound catalytic hydration method
By using the combination of molded molecular sieve support and ion exchange resin in the hydration catalyst, an organic-inorganic interpenetrating network structure is formed, which solves the problem of poor swelling resistance of the catalyst, realizes an efficient epoxy compound hydration reaction, and improves the ethylene glycol Selectivity and conversion rate reduce production costs.
Patent Information
- Application Number
- CN202310815713.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-04
AI Technical Summary
The existing hydration catalysts have poor swelling resistance in the catalytic hydration reaction of epoxy compounds, resulting in the failure of the resin under high hydration ratio, the reactor is blocked, the pressure is increased, and the traditional method is costly and the route is complex, which affects the performance of the catalyst.
The hydration catalyst is prepared by adsorption polymerization, halomethylation, quaternization and other steps to form an organic-inorganic interpenetrating network structure to improve the swelling resistance and catalytic activity of the resin.
The catalyst has achieved good swelling resistance and catalytic activity under high hydration ratio conditions, and can be used continuously multiple times, which improves the selectivity of ethylene glycol and the conversion rate of epoxy compounds, and reduces production costs.
Smart Images

Figure CN119303629A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin catalysts, and in particular to a hydration catalyst and a preparation method and application thereof, and a method for catalyzing hydration of epoxy compounds. Background Art
[0002] Ethylene glycol is an important petrochemical basic organic raw material, mainly used in the production of polyester fibers, antifreeze, lubricants, surfactants, etc. In addition, it can also be used to produce special solvents such as ethylene glycol ethers, and has a wide range of uses.
[0003] At present, there are three main methods for the industrial production of ethylene glycol, including direct hydration of ethylene oxide, coal / syngas to ethylene glycol, and biomass to ethylene glycol. The most important method for producing ethylene glycol in the world today is still ethylene oxide hydration, which is mainly monopolized by Shell, SD, and Dow, and its basic process flow is the same. Usually, the reaction is carried out under the conditions of hydrated ethylene oxide at a molar ratio of 22-25:1, a temperature of 190-200°C, and a pressure of 2.2MPa. Due to the use of excess water, the concentration of ethylene glycol in the crude product is very low, and the subsequent concentration of ethylene glycol consumes a lot of energy. From the perspective of the development requirements of energy conservation and consumption reduction in the chemical industry, the process level needs to be improved and improved. The EO catalytic hydration method for producing MEG has replaced the traditional non-catalytic hydration method with its advantages of low water ratio and high selectivity, which is the development trend of ethylene glycol production technology.
[0004] Strong alkaline anion exchange resin is generally used to prepare ethylene glycol by catalytic hydration of ethylene oxide. However, due to the low strength of the resin itself, the resin undergoes severe swelling as the reaction proceeds, which greatly limits the scope of use of the resin. CN112041292A introduces a method for alleviating resin swelling from a process perspective, using an adiabatic reactor for catalytic hydration of ethylene oxide while maintaining low swelling and high selectivity of the resin. However, the swelling properties of the resin itself are not fundamentally changed. In extreme cases, the resin will eventually break, causing the reactor to become blocked and the pressure to rise.
[0005] Therefore, the preparation of resins with reasonable skeletons and low expansion rates has always been the goal that people have been striving for. At present, two methods are generally used: one is to improve the stability of the material itself, such as DuPont's NafionR, NafionXR, Nafion511, etc. use perfluorosulfonic acid resins, which have good thermal stability and chemical stability. The maximum operating temperature of this series is 180-190°C, but anion resins cannot be prepared. The other is to improve the stability of ion exchange resins by introducing nanomaterials into the raw materials. For example, CN102372830A and CN102372812A introduce a method of introducing carbon nanotubes, graphene or modified graphene into the resin, which can significantly improve the swelling resistance of the catalyst and has good catalytic performance.
[0006] CN101333265B discloses a method for preparing a strong base anion exchange resin with a long spacer arm, wherein the strong base anion exchange resin with a long spacer arm is obtained by amine alkylation, tertiary amination, and quaternization reaction. The operation is simplified by directly introducing primary amine groups into the leucocytes, but the cost of the amine alkylation reagent is high, which is not conducive to expanding production; Keiko K et al. (Power Plant Chemistry, 2002, 4 (6): 349-353) reported a method for preparing an anion exchange resin with a long chain spacer arm between the benzene ring and the nitrogen atom by using functionalized styrene monomers through suspension polymerization and quaternization reaction. The synthesis of the functionalized monomers in this route is complex and the route is long, the product purity will also affect the performance of the final catalyst, and the swelling problem of the resin has not been solved.
[0007] It can be seen that the catalyst currently used for the catalytic hydration reaction of epoxy compounds, while maintaining the catalytic performance of ion exchange resins, research and development of a catalyst with good anti-swelling properties is still a research hotspot for ion exchange resin catalysts for the catalytic hydration of epoxy compounds. Summary of the invention
[0008] The purpose of the present invention is to overcome the problem of poor swelling resistance of existing hydration catalysts, and to provide a hydration catalyst and a preparation method and application thereof, and a method for catalyzing hydration of epoxy compounds. The hydration catalyst has excellent swelling resistance and is used in hydration reactions, such as the reaction of preparing diols by reacting epoxy compounds with deionized water. Under the condition of high hydration ratio, the catalyst has good catalytic activity and the target product has excellent selectivity.
[0009] The first aspect of the present invention provides a hydration catalyst, wherein the catalyst comprises a shaped molecular sieve carrier and an ion exchange resin supported on the carrier,
[0010] The structure of the catalyst is shown in formula (I),
[0011]
[0012] In formula (I), For forming molecular sieve, is a styrene copolymer matrix, R1, R2 and R3 are each independently an alkyl group, M - It is an anion.
[0013] The second aspect of the present invention provides a method for preparing the hydration catalyst described in the first aspect of the present invention, wherein the preparation method comprises: S1 a shaped molecular sieve carrier adsorbed with an oil phase undergoes a polymerization reaction; S2 a solid intermediate obtained by the polymerization reaction undergoes halogenation, quaternization, and ion exchange to obtain the catalyst; wherein the oil phase contains a styrene monomer, a cross-linking agent, and an initiator.
[0014] The third aspect of the present invention provides use of the catalyst described in the first aspect of the present invention in the reaction of preparing diols by hydration of epoxy compounds.
[0015] The fourth aspect of the present invention provides a method for catalytic hydration of an epoxy compound, wherein the method comprises: in the presence of the catalyst described in the first aspect of the present invention, catalytic hydration reaction of the epoxy compound with water.
[0016] The present invention has at least the following beneficial effects:
[0017] The hydrated catalyst shaped molecular sieve carrier of the present invention has good interaction with the ion exchange resin loaded on the carrier, the catalyst has good catalytic activity, and it also has good thermal stability, can effectively solve the swelling problem of the resin catalyst, and can carry out hydration catalytic reaction for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the BET diagram of the hydrated catalyst in Example 1. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides a hydration catalyst, wherein the catalyst comprises a shaped molecular sieve carrier and an ion exchange resin supported on the carrier,
[0021] The structure of the catalyst is shown in formula (I),
[0022]
[0023] In formula (I), For forming molecular sieve, is a styrene copolymer matrix, R1, R2 and R3 are each independently an alkyl group, M - It is an anion.
[0024] In the present invention, the hydrated catalyst including the shaped molecular sieve carrier and the ion exchange resin loaded on the carrier has excellent swelling resistance. At a high hydration ratio, the catalyst has excellent activity and high selectivity for the target product, and the catalyst can be used continuously for multiple times. The inventor speculates that the shaped molecular sieve in the present invention has a pore structure, and the ion exchange resin is between the inner and outer surfaces of the shaped molecular sieve, and has a stable organic-inorganic interpenetrating network structure, so that the hydrated catalyst has good stability and catalytic performance.
[0025] In the present invention, it is understood that in formula (I), Represents the structure of an ion exchange resin.
[0026] According to the present invention, as long as the purpose of the present invention can be achieved, the mass ratio of the ion exchange resin to the carrier is not particularly limited. In some embodiments, the loading amount of the ion exchange resin is 15-55wt%, for example, 15wt%, 25wt%, 29wt%, 35wt%, 35wt%, 40wt% or 55wt%, and the range composed of any two of the above values, preferably 30-45wt%. Using the above embodiment, the hydrated catalyst has excellent catalytic performance and stability.
[0027] In the present invention, the loading amount of the ion exchange resin refers to the percentage of the mass of the ion exchange resin to the total mass of the hydration catalyst.
[0028] According to the present invention, in some embodiments, the specific surface area of the catalyst is 30-500m 2 / g, for example, 30m 2 / g, 40m 2 / g, 50m 2 / g、100m 2 / g, 150m 2 / g or 200m 2 / g, and the range of any two of the above values, preferably 50-200m 2 By adopting the above-mentioned embodiment, the hydrated catalyst has better swelling resistance, more uniform distribution of active sites, good activity when the catalyst is used, and good selectivity of the target product.
[0029] In the present invention, "molded molecular sieve" refers to a shaped molecular sieve having a certain shape prepared by a molecular sieve powder raw material according to a conventional molding method in the art. As long as the purpose of the present invention can be achieved, the shape of the shaped molecular sieve is not particularly limited. In some embodiments, the shape of the shaped molecular sieve is selected from one or more of strip, spherical, columnar, honeycomb and corrugated. With the aforementioned embodiment, there is a strong interaction between the ion exchange resin and the shaped molecular sieve, and the hydrated catalyst has better catalytic activity, stability and swelling resistance.
[0030] According to the present invention, as long as the purpose of the present invention can be achieved, the particle size of the shaped molecular sieve is not particularly limited. In some embodiments, the particle size of the shaped molecular sieve is 0.4-5 mm, preferably 1.3-2.4 mm.
[0031] In the present invention, when the molecular sieve is in the shape of a strip or a column, the particle size of the molecular sieve refers to its height, and when the molecular sieve is in the shape of a sphere, the particle size of the molecular sieve refers to its diameter.
[0032] According to the present invention, in some embodiments, the specific surface area of the shaped molecular sieve is 300-1000m 2 / g, for example, 300m 2 / g, 400m 2 / g, 600m 2 / g、700m 2 / g、1000m 2 / g or 300m 2 / g, and the range of any two of the above values, preferably 400-700m 2 By adopting the above-mentioned embodiment, the hydrated catalyst has more functional active sites and better catalytic performance.
[0033] According to the present invention, in some embodiments, the bulk density of the shaped molecular sieve is 0.4-1.1 g / mL, preferably 0.6-0.9 g / mL. Using the above embodiment, the hydrated catalyst has good stability, swelling resistance and catalytic performance.
[0034] According to the present invention, in some embodiments, the compressive strength of the molded molecular sieve is not less than 30 N, preferably 60-100 N. By adopting the above embodiment, the hydrated catalyst has good stability, swelling resistance and catalytic performance.
[0035] According to the present invention, in some embodiments, the pore size of the formed molecular sieve is 0.1-10nm, for example, 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 1nm, 2nm, 3nm, 5nm, 7nm or 10nm, and the range composed of any two of the above values, preferably 0.3-3nm. Using the above embodiment, the hydrated catalyst has good catalytic activity, its swelling resistance is excellent, and the catalyst can be used continuously for multiple times.
[0036] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the shaped molecular sieve is not particularly limited, and the shaped molecular sieve is selected from one or more of shaped A-type molecular sieve, shaped zeolite-type molecular sieve, shaped X-type molecular sieve, shaped ZSM-type molecular sieve and shaped Y-type molecular sieve. Using the above embodiment, the hydration catalyst has good stability and swelling resistance.
[0037] According to the present invention, in some preferred embodiments, the shaped molecular sieve is a shaped molecular sieve type A. By adopting the above-mentioned embodiment, the hydrated catalyst can provide more active sites, and the catalyst not only has good catalytic activity, but also has excellent swelling resistance and stability.
[0038] According to the present invention, in some preferred embodiments, the molded A-type molecular sieve is one or more of a molded 3A molecular sieve, a molded 4A molecular sieve and a molded 5A molecular sieve. Using the aforementioned embodiments, the hydrated catalyst has good catalytic activity, swelling resistance and stability.
[0039] According to the present invention, in some preferred embodiments, the shaped A-type molecular sieve is a shaped 4A molecular sieve and / or a shaped 5A molecular sieve. Using the above embodiments, the hydrated catalyst has good catalytic activity, swelling resistance and stability.
[0040] According to the present invention, as long as the purpose of the present invention can be achieved, the specific structure of the styrene copolymer matrix is not particularly limited. In some embodiments, the styrene copolymer matrix contains a structural unit A from a monovinyl aromatic monomer and a structural unit B from a cross-linking agent. Using the above embodiment, the hydration catalyst has good catalytic activity and stability.
[0041] According to the present invention, those skilled in the art can select the content of structural unit A and structural unit B as needed. In some embodiments, based on the total mass of structural unit A and structural unit B, the content of structural unit A is 80-98% by mass, and the content of structural unit B is 2-20% by mass. Using the above embodiment, the hydrated catalyst has good catalytic activity, stability and swelling resistance.
[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the type of monovinyl aromatic monomer providing structural unit A is not particularly limited. In some embodiments, the monovinyl aromatic monomer is selected from one or more of styrene, α-methylstyrene, ortho-, meta-, and para-alkylstyrenes.
[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the type of cross-linking agent providing structural unit B is not particularly limited. In some embodiments, the cross-linking agent is selected from one or more of ethylene glycol dimethacrylate, dipropylene glycol, 1,2-bis(4-vinylphenyl)ethane and divinylbenzene.
[0044] In the present invention, "alkyl group" includes branched-chain alkyl groups and branched-chain alkyl groups, and the present invention has no particular limitation thereto.
[0045] According to the present invention, as long as the purpose of the present invention can be achieved, the number of carbon atoms in the alkyl group in R1, R2 and R3 in formula (I) is not particularly limited. In some embodiments, R1, R2 and R3 are each independently a C1-C10 alkyl group, such as a methyl group, an ethyl group, an isopropyl group, an n-propyl group, an n-butyl group, an isobutyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group or a decyl group, preferably a C1-C5 alkyl group. By adopting the above-mentioned embodiment, the hydration catalyst has good stability and catalytic activity.
[0046] According to the present invention, as long as the purpose of the present invention can be achieved, the anion M - There is no particular limitation on the specific type of M. In some embodiments, - Selected from bicarbonate ion, hydroxide ion, bisulfite ion, formate ion, acetate ion or citrate ion.
[0047] The second aspect of the present invention provides a method for preparing the hydration catalyst described in the first aspect of the present invention, wherein the preparation method comprises: S1 a shaped molecular sieve carrier adsorbed with an oil phase undergoes a polymerization reaction; S2 a solid intermediate obtained by the polymerization reaction undergoes halogenation, quaternization, and ion exchange to obtain the catalyst; wherein the oil phase contains a styrene monomer, a cross-linking agent, and an initiator.
[0048] In the present invention, the molded molecular sieve has a pore structure. In the process of preparing the hydration catalyst, small molecule styrene monomers and cross-linking agents can form styrene copolymer molecular chains in the presence of an initiator and load them on the inner and outer surfaces of the molded molecular sieve, thereby forming a stable organic-inorganic interpenetrating network structure. Finally, halomethylation, quaternization, and ion exchange reaction functionalization reactions are carried out, so that the prepared catalyst not only has excellent stability and swelling resistance, but also has better catalytic properties.
[0049] According to the present invention, it can be understood that the "molded molecular sieve carrier adsorbed with an oil phase" is a molded molecular sieve whose inner and outer surfaces are adsorbed with an oil phase containing a styrene monomer, a cross-linking agent and an initiator. As long as the purpose of the present invention can be achieved, the method for obtaining the molded molecular sieve carrier adsorbed with an oil phase is not particularly limited. In some embodiments, the method for obtaining the molded molecular sieve carrier adsorbed with an oil phase includes: immersing the oil phase in contact with the molded molecular sieve carrier and then filtering to obtain the molded molecular sieve carrier adsorbed with the oil phase.
[0050] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions for soaking and contacting are not particularly limited, for example, the conditions for soaking and contacting include: room temperature (referring to 15-25° C.); and / or soaking time is 12-36 hours. The above embodiment can ensure that the shaped molecular sieve fully absorbs the oil phase.
[0051] According to the present invention, as long as the purpose of the present invention can be achieved, when preparing the hydration catalyst, the amount of each raw material is not particularly limited. In some embodiments, based on the total mass of the oil phase and the formed molecular sieve, the amount of the styrene monomer is 35-60% by mass, the amount of the cross-linking agent is 2-10% by mass, the amount of the initiator is 0.1-3% by mass, and the amount of the formed molecular sieve is 30-60% by mass. Using the above embodiment, the prepared hydration catalyst has excellent catalytic activity and stability.
[0052] According to the present invention, those skilled in the art can select the type of initiator according to needs. In some embodiments, the initiator is an azo initiator and / or a peroxide initiator.
[0053] In the present invention, the azo initiators include azobisisobutyronitrile, azobisisoheptylnitrile and the like; the peroxide initiators include benzoyl peroxide, lauroyl peroxide and cumene hydroperoxide and the like.
[0054] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the polymerization reaction are not particularly limited. In some embodiments, the conditions of the polymerization reaction include: a reaction temperature of 80-100° C. According to the present invention, in some embodiments, the conditions of the polymerization reaction include: a reaction time of 4-12 hours.
[0055] According to the present invention, it can be understood that the styrene monomer, the cross-linking agent and the initiator will be polymerized and cross-linked in the pores of the molded molecular sieve and / or on its surface to obtain a resin polymer, and finally form a solid intermediate molecular sieve / resin, on the surface of which some raw materials may still remain. The mixture obtained after the polymerization reaction can be washed and dried to obtain the solid intermediate; for example, methanol can be used for elution; drying is a conventional drying method in the art and will not be elaborated in the present invention.
[0056] According to the present invention, those skilled in the art can select a halomethylation method as needed. In some embodiments, the halomethylation method includes: mixing a solid intermediate (molecular sieve / resin) with a halomethylation agent, then adding a Lewis acid catalyst to carry out a halomethylation reaction, cooling to room temperature, filtering out the halogenated mother liquor, repeatedly washing with methanol several times, and finally drying to obtain a halomethylation product; wherein the mixing method is not particularly limited, and preferably the mixture is allowed to stand for 1-5 hours after mixing before adding the Lewis acid catalyst.
[0057] According to the present invention, as long as the purpose of the present invention can be achieved, there is no special limitation on the amount of the solid intermediate (molecular sieve / resin) and the halomethylation agent. In some embodiments, molecular sieve / resin ball: halomethylation agent = (1-10) g: (10-30) mL.
[0058] According to the present invention, in some embodiments, the halomethylating agent is selected from one or more of chloromethyl methyl ether (chloromethyl ether), bromomethyl methyl ether, chloromethyl ethyl ether and bromomethyl ethyl ether.
[0059] According to the present invention, in order to enable the halomethylation reaction to proceed smoothly, those skilled in the art can select the amount and type of Lewis acid catalyst as needed. In some embodiments, the mass of the Lewis acid catalyst is 2-10wt% of the mass of the molecular sieve / resin ball.
[0060] According to the present invention, the Lewis acid catalyst may be selected from zinc chloride, zinc bromide, ferric chloride, ferric bromide, tin tetrachloride and the like.
[0061] According to the present invention, in some embodiments, the conditions of the halomethylation reaction include: the reaction temperature is 50-60°C.
[0062] According to the present invention, in some embodiments, the conditions of the halomethylation reaction include: the reaction time is 5-15 hours.
[0063] According to the present invention, those skilled in the art can understand that after the halomethylation is completed, impurities and halogenated mother liquor may still exist. After the halomethylation is completed, the halogenated mother liquor can be filtered out, and the solid product can be repeatedly washed with methanol for multiple times and dried to obtain the halomethylated product, and then the halomethylated product is taken for quaternization.
[0064] According to the present invention, those skilled in the art can select a quaternization method as needed. In some embodiments, the quaternization method includes: in the presence of a solvent, the halomethylated product is subjected to a quaternization reaction with a quaternizing agent, and then cooled to room temperature, followed by filtering to remove the reaction solution, and then washing with ethyl acetate, 0.05-0.15 mol / L HCl aqueous solution, and water in sequence, and then drying (e.g., vacuum drying at 50-70° C. for 8-15 hours) to obtain a molecular sieve / ammonium resin.
[0065] According to the present invention, as long as the quaternization reaction can be smoothly carried out, the amount of the solvent is not particularly limited. In some embodiments, solvent: halomethylation product = 10 mL: (1-8) g.
[0066] According to the present invention, in some embodiments, the solvent is selected from one or more of N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide and dimethyl sulfoxide.
[0067] According to the present invention, in some embodiments, the halomethylation product: quaternization agent = (1-5) g: 5 mL.
[0068] According to the present invention, in some embodiments, the conditions of the quaternization reaction include: the reaction temperature is 50-70°C.
[0069] According to the present invention, in some embodiments, the conditions of the quaternization reaction include: the reaction time is 12-36 hours.
[0070] According to the present invention, those skilled in the art can select a quaternary ammonium ion exchange method according to their needs. In some embodiments, the ion exchange method includes: mixing a molecular sieve / ammonium resin with a quaternary ammonium resin containing M - The salt or alkali aqueous solution of the group is subjected to ion exchange reaction, and then washed with deionized water until the pH of the washing solution is 7, and finally dried to obtain the catalyst.
[0071] According to the present invention, when quaternization is carried out, a compound containing M may be added as required. - Aqueous solution of salt or base of a group, such as molecular sieve / ammonium resin: containing M - Aqueous solution of salt or base of a group = 1g: (10-50) mL, preferably containing M - The concentration of the aqueous solution of the salt or base of the radical is 0.1-0.5 mol / L.
[0072] According to the present invention, the conditions for the ion exchange reaction are not particularly limited. The ion exchange reaction is preferably carried out under stirring at room temperature. The ion exchange reaction time is preferably 12-48 hours.
[0073] The third aspect of the present invention provides use of the catalyst described in the first aspect of the present invention in the reaction of preparing diols by hydration of epoxy compounds.
[0074] In the present invention, the catalyst of the present invention is used in the hydration reaction of epoxy compounds. The catalyst not only has good catalytic activity and selectivity for diols, but also has excellent swelling resistance, and the catalyst can be used continuously for multiple times.
[0075] The fourth aspect of the present invention provides a method for catalytic hydration of an epoxy compound, wherein the method comprises: in the presence of the catalyst described in the first aspect of the present invention, catalytic hydration reaction of the epoxy compound with water.
[0076] In the present invention, in the presence of the catalyst of the present invention, the epoxy compound and water undergo a catalytic hydration reaction, the epoxy compound has a high conversion rate, the diol has a high yield, and the catalyst has excellent swelling resistance and can maintain good catalytic activity during continuous use.
[0077] According to the present invention, the specific type of epoxy compound can be selected as needed. In some embodiments, the epoxy compound is selected from ethylene oxide, propylene oxide or styrene oxide.
[0078] According to the present invention, the conditions for the hydration reaction can be selected as needed. In some embodiments, the conditions for the hydration reaction include: a molar ratio of water to epoxy compound of (1-50):1, preferably (6-20):1.
[0079] According to the present invention, in some embodiments, the conditions of the hydration reaction include: the reaction temperature is 40-180°C, preferably 80-110°C.
[0080] According to the present invention, in some embodiments, the conditions of the hydration reaction include: the reaction pressure is 0.1-10.0 MPa, preferably 1.0-2.5 MPa.
[0081] According to the present invention, in some embodiments, the liquid space velocity is 0.5-3h -1 .
[0082] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0083] The prepared hydration catalysts were loaded into fixed bed reactors to carry out the catalytic hydration reaction of ethylene oxide to prepare ethylene glycol. The conditions were as follows: reaction temperature was 90°C; the molar ratio of water to ethylene oxide was 9:1; the liquid space velocity was 1.5 h -1 ; The reaction pressure is 1.2Mpa.
[0084] Example 1
[0085] In a 500 ml flask, add 150 g of styrene, 12 g of divinylbenzene, and 3 g of benzoyl peroxide. After stirring for 1 hour, add 100 g of spherical 5A molecular sieve (particle size 2.2 mm; specific surface area 390 m 2 / g; bulk density is 0.69g / ml; compressive strength is 65N; pore size is 0.5nm), soaked at room temperature for 24 hours, then the oil phase is filtered to obtain a molecular sieve adsorbed with the oil phase, which is placed at 90°C for reaction for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin;
[0086] In a 500mL three-necked flask, add 60g of molecular sieve / resin and 200mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 5g of zinc chloride as a catalyst and start stirring, gradually heat to 60°C and react for 10 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash repeatedly with methanol 3 times, and dry at 100°C for 8 hours to obtain a molecular sieve / chlororesin;
[0087] In a 500 mL three-necked flask, 60 g of molecular sieve / chlorine resin balls, 100 ml of tributylamine, and 200 ml of N,N-dimethylformamide were added, reacted at 60° C. for 24 hours, and then cooled to room temperature. The reaction solution was then filtered to remove the reaction solution, and then washed with ethyl acetate, 0.1 mol / L HCl, and deionized water in sequence, and then dried at 60° C. in vacuum for 12 hours to obtain molecular sieve / ammonium resin balls;
[0088] In a 1000mL three-necked flask, 20g of molecular sieve / ammonium resin and 800mL of a 0.1mol / L NaHCO3 deionized water solution were added and stirred at room temperature for ion exchange reaction for 24 hours; then washed with deionized water until the pH of the washing solution was 7, and vacuum dried to obtain a hydrated catalyst, which was recorded as Cat-A1.
[0089] The structure of the obtained hydration catalyst is:
[0090] It is a spherical 5A molecular sieve. It is a styrene copolymer matrix;
[0091] In the hydrated catalyst, the loading amount of the ion exchange resin is 36 wt%; the specific surface area of the catalyst is 60 m 2 / g.
[0092] The BET diagram of the hydrated catalyst is shown in Figure 1 shown.
[0093] Cat-A1 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 99.8% and the selectivity of ethylene glycol was 98.9%.
[0094] Example 2
[0095] In a 500 ml flask, add 150 g of α-methylstyrene, 18 g of ethylene glycol dimethacrylate, and 4 g of benzoyl peroxide. After stirring for 1 hour, add 100 g of columnar 3A molecular sieve (particle size 1.5 mm; specific surface area 500 m 2 / g; bulk density is 0.68g / ml; compressive strength is 80N; pore size is 0.3nm), soaked at room temperature for 15 hours, then the oil phase is filtered to obtain a molecular sieve adsorbed with the oil phase, which is placed at 90°C for reaction for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin;
[0096] In a 500mL three-necked flask, add 100g of molecular sieve / resin and 300mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 8g of zinc chloride as a catalyst and start stirring, gradually heat to 60°C and react for 12 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash repeatedly with methanol 3 times, and dry at 100°C for 8 hours to obtain a molecular sieve / chlororesin;
[0097] Add 90 g of molecular sieve / chlorine resin balls, 150 ml of tributylamine and 200 ml of N,N-dimethylformamide into a 500 mL three-necked flask, react at 60° C. for 24 hours, then cool to room temperature, filter out the reaction solution, wash with ethyl acetate, 0.1 mol / L HCl and deionized water in sequence, and then dry at 60° C. in vacuum for 12 hours to obtain molecular sieve / ammonium resin balls;
[0098] In a 1000mL three-necked flask, 20g of molecular sieve / ammonium resin and 400mL of a 0.25mol / L NaHCO3 deionized water solution were added and stirred at room temperature for ion exchange reaction for 24 hours; then washed with deionized water until the pH of the washing solution was 7, and vacuum dried to obtain a hydrated catalyst, which was recorded as Cat-A2.
[0099] The structure of the obtained hydration catalyst is:
[0100] It is a spherical 3A molecular sieve. It is a styrene copolymer matrix;
[0101] In the hydrated catalyst, the loading amount of the ion exchange resin is 41 wt%; the specific surface area of the catalyst is 190 m 2 / g.
[0102] Cat-A2 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 97.5% and the selectivity of ethylene glycol was 98.6%.
[0103] Example 3
[0104] In a 500 ml flask, add 150 g of styrene, 20 g of divinylphenylmethane, and 5 g of benzoyl peroxide. After stirring for 1 hour, add 100 g of spherical 4A molecular sieve (particle size 3.2 mm; specific surface area 900 m 2 / g; bulk density is 0.64g / ml; compressive strength is 85N; pore size is 0.4nm), soaked at room temperature for 12 hours, then the oil phase is filtered to obtain a molecular sieve adsorbed with the oil phase, which is placed at 90°C for reaction for 10 hours, then rinsed with methanol and dried to obtain a molecular sieve / resin;
[0105] In a 500mL three-necked flask, add 100g of molecular sieve / resin and 300mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 3g of zinc chloride as a catalyst and start stirring, gradually heat to 50°C and react for 12 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash repeatedly with methanol 3 times, and dry at 100°C for 8 hours to obtain a molecular sieve / chlororesin;
[0106] In a 500 mL three-necked flask, 60 g of molecular sieve / chlorine resin balls, 150 ml of tributylamine, and 200 ml of N,N-dimethylformamide were added, reacted at 50° C. for 36 hours, and then cooled to room temperature. The reaction solution was then filtered to remove the reaction solution, and then washed with ethyl acetate, 0.15 mol / L HCl, and deionized water in sequence, and then dried at 60° C. in vacuum for 12 hours to obtain molecular sieve / ammonium resin balls;
[0107] In a 1000mL three-necked flask, 20g of molecular sieve / ammonium resin and 500mL of a 0.2mol / L NaHCO3 deionized water solution were added and stirred at room temperature for ion exchange reaction for 24 hours; then washed with deionized water until the pH of the washing solution was 7, and vacuum dried to obtain a hydrated catalyst, recorded as Cat-A3.
[0108] The structure of the obtained hydration catalyst is:
[0109] It is a spherical 4A molecular sieve. It is a styrene copolymer matrix;
[0110] In the hydrated catalyst, the loading amount of the ion exchange resin is 38 wt%; the specific surface area of the catalyst is 300 m 2 / g.
[0111] Cat-A3 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 99.7% and the selectivity of ethylene glycol was 98.5%.
[0112] Example 4
[0113] The method of Example 1 is followed except that a spherical ZSM-5 molecular sieve (particle size 2-3 mm; specific surface area 360 m 2 / g; bulk density is 0.7g / mL; compressive strength is 70; pore size is 0.58nm) to replace the spherical 5A molecular sieve;
[0114] The structure of the obtained hydration catalyst is:
[0115] It is ZSM-5 molecular sieve, It is a styrene copolymer matrix;
[0116] In the hydrated catalyst, the loading amount of the ion exchange resin is 35wt%; the specific surface area of the catalyst is 80m 2 / g;
[0117] The hydration catalyst finally prepared was recorded as Cat-A4;
[0118] Cat-A4 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 98.6% and the selectivity of ethylene glycol was 93.7%.
[0119] Example 5
[0120] The method of Example 1 was followed except that spherical 13X molecular sieve (particle size 5 mm, specific surface area 950 m 2 / g; bulk density is 0.6g / mL; compressive strength is 30N; pore size is 1.0nm) to replace the spherical 5A molecular sieve;
[0121] The structure of the obtained hydration catalyst is:
[0122] It is a spherical 13X molecular sieve. It is a styrene copolymer matrix;
[0123] In the hydrated catalyst, the loading amount of the ion exchange resin is 40 wt%; the specific surface area of the catalyst is 100 m 2 / g;
[0124] The hydration catalyst finally prepared was recorded as Cat-A5;
[0125] Cat-A5 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 96.6% and the selectivity of ethylene glycol was 97.3%.
[0126] Example 6
[0127] The method of Example 1 is followed, except that triheptylamine is used as a reaction reagent instead of tributylamine. The structure of the obtained hydration catalyst is:
[0128] It is a spherical 5A molecular sieve. It is a styrene copolymer matrix;
[0129] In the hydrated catalyst, the loading amount of the ion exchange resin is 16 wt%; the specific surface area of the catalyst is 100 m 2 / g;
[0130] The hydration catalyst finally prepared was recorded as Cat-A6;
[0131] Cat-A6 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 95.6% and the selectivity of ethylene glycol was 98.5%.
[0132] Comparative Example 1
[0133] In a 500 ml flask, add 150 g of styrene, 12 g of divinylbenzene, and 1 g of benzoyl peroxide. Stir for 30 minutes and then add 100 g of unformed powdered 5A molecular sieve (particle size of 2 to 4 microns; specific surface area of 900 m 2 / g; bulk density is 0.43g / mL; pore size is 0.5nm), soaked at room temperature for 24 hours, then filtered the oil phase to obtain the adsorbed molecular sieve, placed it at 90°C for reaction for 10 hours, then rinsed with methanol and dried to obtain molecular sieve / resin ball B1;
[0134] In a 500mL three-necked flask, add 60g of molecular sieve / resin ball B1 and 200mL of chloromethyl ether, let stand at room temperature for 2 hours, then add 15g of zinc chloride as a catalyst and start stirring, gradually heat to 60°C and react for 10 hours, cool to room temperature after the reaction, filter out the chlorinated mother liquor, wash repeatedly with methanol 3 times, and dry at 100°C for 8 hours to obtain molecular sieve / resin chlorine ball B1;
[0135] In a 500 mL three-necked flask, add 60 g of molecular sieve / resin chloride ball A1, 100 ml of tributylamine, and 200 ml of N,N-dimethylformamide, react at 60°C for 24 hours, then cool to room temperature, filter out the reaction solution, wash with ethyl acetate, 0.1 mol / L HCl, and deionized water in sequence, and then dry at 60°C in vacuum for 12 hours to obtain molecular sieve / resin ammonium ball B1;
[0136] In a 1000mL three-necked flask, 50g of molecular sieve / resin ammonium ball B1 and 2000mL of a 0.1mol / L NaHCO3 deionized water solution were added and stirred at room temperature for ion exchange reaction for 24 hours; then washed with deionized water until the pH of the washing solution was 7, vacuum dried, and finally rolled into a hydrated catalyst with a diameter of 2mm, recorded as Cat-B1.
[0137] In the hydrated catalyst, the content of ion exchange resin is 25wt%; the specific surface area of the catalyst is 39m 2 / g;
[0138] Cat-B1 was used to carry out the test of preparing ethylene glycol by catalytic hydration reaction of ethylene oxide. The conversion rate of ethylene oxide was 85.3% and the selectivity of ethylene glycol was 93.1%.
[0139] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydration catalyst, characterized in that The catalyst comprises a shaped molecular sieve carrier and an ion exchange resin loaded on the carrier. The structure of the catalyst is shown in formula (I), In formula (I), For forming molecular sieve, is a styrene copolymer matrix, R1, R2 and R3 are each independently an alkyl group, M - It is an anion.
2. The catalyst according to claim 1, wherein The loading amount of the ion exchange resin is 15-55wt%, preferably 30-45wt%; and / or The specific surface area of the catalyst is 30-500m 2 / g, preferably 50-200m 2 / g.
3. The catalyst according to claim 1 or 2, wherein The shape of the shaped molecular sieve is selected from one or more of strip, spherical, columnar, honeycomb and corrugated; and / or The particle size of the shaped molecular sieve is 0.4-5 mm, preferably 1.3-2.4 mm; and / or The specific surface area of the shaped molecular sieve is 300-1000m 2 / g, preferably 400-700m 2 / g; and / or The bulk density of the shaped molecular sieve is 0.4-1.1 g / mL, preferably 0.6-0.9 g / mL; and / or The compressive strength of the molded molecular sieve is not less than 30N, preferably 60-100N; and / or The pore size of the shaped molecular sieve is 0.1-10 nm, preferably 0.3-3 nm.
4. The catalyst according to any one of claims 1 to 3, wherein The molded molecular sieve is one or more of a molded A-type molecular sieve, a molded zeolite-type molecular sieve, a molded X-type molecular sieve, a molded ZSM-type molecular sieve and a molded Y-type molecular sieve, preferably a molded A-type molecular sieve; Preferably, the shaped A-type molecular sieve is one or more of shaped 3A molecular sieve, shaped 4A molecular sieve and shaped 5A molecular sieve, preferably shaped 4A molecular sieve and / or shaped 5A molecular sieve.
5. The catalyst according to any one of claims 1 to 4, wherein The styrene copolymer matrix contains a structural unit A derived from a monovinyl aromatic monomer and a structural unit B derived from a crosslinking agent; Preferably, based on the total mass of the structural unit A and the structural unit B, the content of the structural unit A is 80-98 mass %, and the content of the structural unit B is 2-20 mass %; and / or The monovinyl aromatic monomer is selected from one or more of styrene, α-methylstyrene, o-, m-, and p-alkylstyrene; and / or The crosslinking agent is selected from one or more of ethylene glycol dimethacrylate, dipropylene benzene, 1,2-bis(4-vinylphenyl)ethane and divinyl benzene.
6. The catalyst according to any one of claims 1 to 5, wherein R1, R2 and R3 are each independently a C1-C10 alkyl group, preferably a C1-C5 alkyl group; and / or M - Selected from bicarbonate ion, hydroxide ion, bisulfite ion, formate ion, acetate ion or citrate ion.
7. A method for preparing the catalyst according to any one of claims 1 to 6, characterized in that: The preparation method comprises: S1 is a shaped molecular sieve carrier adsorbed with oil phase for polymerization reaction; S2 The solid intermediate obtained by the polymerization reaction is subjected to halomethylation, quaternization, and ion exchange to obtain the catalyst; Wherein, the oil phase contains styrene monomers, a cross-linking agent and an initiator.
8. The preparation method according to claim 7, wherein: The method for obtaining a shaped molecular sieve carrier adsorbed with an oil phase comprises: filtering the shaped molecular sieve carrier adsorbed with the oil phase after immersing the oil phase in contact with the shaped molecular sieve carrier; preferably, based on the total mass of the oil phase and the shaped molecular sieve, the amount of the styrene monomer is 35-60% by mass, the amount of the crosslinking agent is 2-10% by mass, the amount of the initiator is 0.1-3% by mass, and the amount of the shaped molecular sieve is 30-60% by mass; and / or The conditions of the polymerization reaction include: a reaction temperature of 80-100° C. and / or a reaction time of 4-12 hours.
9. Use of the catalyst according to any one of claims 1 to 6 in the reaction of preparing diols by hydration of epoxy compounds.
10. A method for catalytic hydration of an epoxy compound, characterized in that: The method includes: In the presence of a catalyst according to any one of claims 1 to 6, the epoxy compound and water undergo a catalytic hydration reaction; Preferably, The epoxy compound is selected from ethylene oxide, propylene oxide or styrene oxide; and / or The conditions of the hydration reaction include: The molar ratio of water to epoxy compound is (1-50):1, preferably (6-20):1; and / or The reaction temperature is 40-180°C, preferably 80-110°C; and / or The reaction pressure is 0.1-10.0 MPa, preferably 1.0-2.5 MPa; and / or Liquid space velocity is 0.5-3h -1 .
Citation Information
Patent Citations
Alkene hydration method
CN102757309A
Molecular sieve supported ionic liquid catalyst and polyoxymethylene dimethyl ether catalyzed synthesis method thereof
CN103381372A
Basic monolithic catalyst with regular pore channels, preparation method of catalyst and application of catalyst in MIBK synthesis process
CN108126748A
Method for preparing glycerol monoether from glycerol
CN114591153A
Low-carbon olefin polymerization catalyst as well as preparation method and application thereof
CN116020542A
Cited By
Phase-transfer enrichment functional catalyst for preparing 3-hydroxypropionaldehyde through acrolein hydration reaction as well as preparation method and application of phase-transfer enrichment functional catalyst
CN122080492A